2002
DOI: 10.1099/00221287-148-11-3705
|View full text |Cite
|
Sign up to set email alerts
|

Copper- and zinc-containing superoxide dismutase (Cu/ZnSOD) is required for the protection of Candida albicans against oxidative stresses and the expression of its full virulence

Abstract: Copper-and zinc-containing superoxide dismutase (Cu/ZnSOD) is suspected to be one of the anti-oxidant enzymes and virulence determinants active in some pathogenic micro-organisms. To elucidate the role of Cu/ZnSOD in the major human fungal pathogen Candida albicans, its gene, designated SOD1, was disrupted by the URA-blaster technique. The resulting sod1/sod1 mutant showed delayed hyphal growth on Spider medium but could still form hyphae on other solid media or in liquid media, particularly in response to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
182
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(195 citation statements)
references
References 37 publications
11
182
1
1
Order By: Relevance
“…Moreover, it was found that a manganese-type SOD-encoding gene is upregulated during conidiogenesis of the plant-pathogenic fungus Colletotrichum graminicola (Fang et al, 2002), and Candida albicans, lacking the SOD gene, showed delayed hyphal growth necessary for the full virulence of the organism to be expressed (Hwang et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that a manganese-type SOD-encoding gene is upregulated during conidiogenesis of the plant-pathogenic fungus Colletotrichum graminicola (Fang et al, 2002), and Candida albicans, lacking the SOD gene, showed delayed hyphal growth necessary for the full virulence of the organism to be expressed (Hwang et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…However, while sod1Δ is hypersensitive to killing by a macrophage cell line in vitro (Hwang et al 2002), the same was not observed for sod5Δ (Martchenko et al 2004), indicating that the virulence role of Sod5 may be due to a resistance to different phagocytic cells. Frohner et al (2009) recently demonstrated that the Sod4 and Sod5 produced by innate immune response cells are extremely important as ROS scavengers.…”
mentioning
confidence: 81%
“…As mentioned, previous studies have demonstrated that the SOD1 gene and GRX2 gene play a role in the virulence of C. albicans (Hwang et al 2002, Chaves et al 2007). When separately disrupted, these genes led to an attenuation of virulence in an animal model of systemic infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations